PENGARUH REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION (RTMS) TERHADAP GANGGUAN FUNGSI KOGNITIF PASCASTROKE ISKEMIK - Novika Azirah Azis; Jumraini Tammasse; Abdul Muis (PERDOSNI, 2019)
THE INFLUENCE OF REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION (RTMS) TOWARDS IMPAIRED COGNITIVE FUNCTION AFTER ISCHEMIC STROKEABSTRACTIntroduction: The increasing number of ischemic stroke patients who experience memory disturbances and a long rehabilitation process requires an innovation that can strengthen both existing therapies (medical therapy) and non-invasive stimulation of cognitive rehabilitation in the form of repetitive transcranial magnetic stimulation (rTMS).Aim: To determine effectiveness of rTMS towards impaired cognitive function in ischemic stroke.Methods: This research was conducted using experimental with open clinical trial test method on ischemic stroke patients suffering from cognitive impairment at Wahidin Sudirohusodo Hospital and Inggit Clinic, Makassar, from November 2018 until January 2019. Samples were divided into control who was given only medical therapy and treatment group who was given medical therapy and rTMS. Stimulation is given in the form of a high frequency of 10Hz in 2 cycles for 5 consecutive days with a gap of 2 days. MoCA-Ina was used to assess cognitive impairment. The assessment were made on day-1 before therapy and day-15 after therapy. The statistical analysis of correlation among variables was conducted by using Chi-square test with value of p <0.05 which was considered significant.Results: There were 22 samples, 11 in each group. The difference of MoCA-Ina scores in both groups with the final average after 15 days of treatment was 5.27 in the treatment group and 1.45 in control group. This difference is considered significant with the p value of 0.003.Discussion: There was an effect of rTMS therapy on cognitive function disorders after ischemic stroke, in which the change was greater in the treatment group than in the control group.Keywords: Cognitive impairment, ischemic stroke, Montreal Cognitive Assesment Indonesian Version (MoCA-Ina), repetitive transcranial magnetic stimulation (rTMS)ABSTRAKPendahuluan: Peningkatan jumlah pasien stroke iskemik yang mengalami gangguan memori serta proses rehabilitasi yang lama membutuhkan suatu inovasi yang dapat saling menguatkan antara terapi yang sudah ada (terapi medik) dan stimulasi non-invasif rehabilitasi kognitif berupa repetitive transcranial magnetic stimulation (rTMS).Tujuan: Mengetahui pengaruh intervensi rTMS terhadap fungsi kognitif pascastroke iskemik.Metode: Penelitian eksperimental dengan uji klinis terbuka terhadap pasien stroke iskemik yang menderita gangguan fungsi kognitif di RSUP Dr. Wahidin Sudirohusodo dan Klinik Inggit Medika, Makassar, pada bulan November 2018 hingga Januari 2019. Subjek dibagi ke dalam kelompok kontrol yang diberikan terapi medikamentosa saja serta kelompok perlakuan yang diberikan terapi medikamentosa dan intervensi rTMS. Stimulasi diberikan berupa frekuensi tinggi 10Hz dalam 2 siklus selama 5 hari berturut-turut dengan jeda waktu 2 hari. Penilaian gangguan kognitif menggunakan Montreal Cognitive Assesment versi Indonesia (MoCA-Ina). Pengukuran dilakukan pada hari-1 pre-terapi dan hari ke-15 pascaterapi. Data dianalisis secara statistik menggunakan uji Chi-square dengan nilai p<0,05 dianggap bermakna.Hasil: Terdapat 22 subjek yang masing-masing terdiri dari 11 subjek pada kelompok kontrol dan perlakuan. Selisih skor MoCA-Ina pada kedua kelompok dengan rerata akhir setelah lima belas hari perlakuan sebesar 5,27 pada kelompok perlakuan dan 1,45 pada kelompok kontrol yang bermakna (p=0,003).Diskusi: Terdapat pengaruh terapi rTMS terhadap gangguan fungsi kognitif pascastroke yang lebih besar pada kelompok perlakuan dibanding kelompok kontrol.Kata kunci: Gangguan kognitif, Montreal Cognitive Assesment versi Indonesia (MoCA-Ina), repetitive transcranial magnetic stimulation (rTMS), stroke iskemik